Effect of Schooling Years, Minimum Wages, and Population Growth on Open Unemployment in Bojonegoro - Syifaul Fuaadhilah Kholis; Heny Musfidah; Dhiah Fitrayati; Shochrul Rohmatul Ajija (Universitas Negeri Surabaya, 2026)
Objective: This study aims to analyze the effect of Average School Length, Minimum Wage, and Population Growth Rate on the Open Unemployment Rate in Bojonegoro Regency for the 2005–2024 period. The research uses a quantitative approach with secondary data obtained from the Central Statistics Agency and related literature. Method: The analysis was performed through multiple linear regression using time series data with a series of classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Results: Show that some variables of population growth rate do not have a significant influence on the Open Unemployment Rate. Meanwhile, the variables of average length of school and minimum wage have a significant and positive influence on the Open Unemployment Rate, which means that these two variables have the potential to lower the open unemployment rate. At the same time, the three independent variables have been proven to have a significant influence on the Open Unemployment Rate. An Adjusted R-Squared (R²) value of 0.687 indicates that 68.7% variation in the Open Unemployment Rate can be explained by Average School Length, Minimum Wage, and Population Growth Rate. Novelty: These findings emphasize the importance of controlling population growth and expanding employment opportunities, especially for highly educated graduates who dominate open unemployment in Bojonegoro. The results of the research are expected to be the basis for local governments in formulating more targeted employment and education policies.